The importance of student motiva The importance of student motivation: The importance of student motivation - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: The article discusses the role of motivation in teaching and learning and its importance to achieve their desired goals. Before teaching or learning first arising the students’ interest is curtail for teachers to make the students go further in spite of the possible challenges and hard work in the process. The article also discusses two types of motivation and their role to make the students feel responsibility.